If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.50(6 + -1y) = y (6 * 0.50 + -1y * 0.50) = y (3 + -0.5y) = y Solving 3 + -0.5y = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 3 + -0.5y + -1y = y + -1y Combine like terms: -0.5y + -1y = -1.5y 3 + -1.5y = y + -1y Combine like terms: y + -1y = 0 3 + -1.5y = 0 Add '-3' to each side of the equation. 3 + -3 + -1.5y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1.5y = 0 + -3 -1.5y = 0 + -3 Combine like terms: 0 + -3 = -3 -1.5y = -3 Divide each side by '-1.5'. y = 2 Simplifying y = 2
| -10.2x=71.4 | | 4x^2-33x+41=-9x+6 | | 6t=-46 | | 5x-9=4(x-3) | | 5p=-15 | | -9(2b+3)+(19b-3)=0 | | 7y^2-8y+15-11y^2-8y+6= | | a^2+8a=9 | | x=-11 | | -(3x+5)+1-4(x-2)+5x-2=0 | | x^2-2x+4=8x-4 | | t^2-10t-24=0 | | x^2+12x+6=0 | | 4x+3(2x-8)=8x-40 | | 4.5x-3.8y+6.9x-0.2y= | | 2s+7=10s-7 | | 27+2x+3=5x | | 2s+7=10-7 | | X^2-2x+4=-8x-4 | | 5x+63=7(x-9) | | n-7=13 | | x+2/3= | | x^2-2x=21 | | X^2-4x+5=10 | | -5(3x+7)=-15 | | 7x-9=2x+21 | | 3x-9y-8x+7y= | | x+2= | | x^2+2x=19 | | 6(5z-1)-4(z+6)=3(z+1) | | X^2-10+16=0 | | 4(x+2)-6=2x-7 |